8(x+6)=7(x-6)+6

Simple and best practice solution for 8(x+6)=7(x-6)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+6)=7(x-6)+6 equation:


Simplifying
8(x + 6) = 7(x + -6) + 6

Reorder the terms:
8(6 + x) = 7(x + -6) + 6
(6 * 8 + x * 8) = 7(x + -6) + 6
(48 + 8x) = 7(x + -6) + 6

Reorder the terms:
48 + 8x = 7(-6 + x) + 6
48 + 8x = (-6 * 7 + x * 7) + 6
48 + 8x = (-42 + 7x) + 6

Reorder the terms:
48 + 8x = -42 + 6 + 7x

Combine like terms: -42 + 6 = -36
48 + 8x = -36 + 7x

Solving
48 + 8x = -36 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
48 + 8x + -7x = -36 + 7x + -7x

Combine like terms: 8x + -7x = 1x
48 + 1x = -36 + 7x + -7x

Combine like terms: 7x + -7x = 0
48 + 1x = -36 + 0
48 + 1x = -36

Add '-48' to each side of the equation.
48 + -48 + 1x = -36 + -48

Combine like terms: 48 + -48 = 0
0 + 1x = -36 + -48
1x = -36 + -48

Combine like terms: -36 + -48 = -84
1x = -84

Divide each side by '1'.
x = -84

Simplifying
x = -84

See similar equations:

| 1+5w=2w-2 | | 2.5p=3 | | 16csquared=48 | | 2x+6=5x-15 | | 2*-4+3y=5*-4-y | | h(h+5)=84 | | 40a=50 | | 2log(4x)=9 | | 4x+8z=2+5y | | 3x^2-90x+950=0 | | G+(-15)forg=-12 | | -5(5n+3)=15 | | 19t-5=5 | | 4y^3-24y^2+20y= | | 29=40x | | 2r+45=15-45 | | -6z+15=3-15 | | 11Y+8=4Y+36 | | X+Y-10=66 | | 19t-5=-5 | | x+8x+(x+100)=710 | | 10+x=5(x-6)+33 | | (79+x+y)3=79 | | x^2-65=8x | | 49=c/3 | | 10b^2=64+72b | | c/4=15 | | 14=c/5 | | c/15=11 | | 2w^2-11w+24=w^2-36 | | 35=5-10W | | x-2/7=3 |

Equations solver categories